Critical Juridical Analysis of the Criminal and Medical Boundaries in the Handling of Narcotics Addicts in Indonesia - Dimas Galih Romadhon (Indonesian Journal Publisher, 2026)
This study examines the proportionality of sentencing in narcotics cases involving intermediary offenders, with particular reference to Supreme Court Decision Number 1944 PK/Pid.Sus/2025. The research is grounded in the persistent issue of disproportionate penal practices, where individuals with minimal and non-decisive roles in drug distribution networks are frequently subjected to severe punishment. The objective of this study is to analyze how judicial reasoning reflects the principles of proportionality and individualization within the framework of Indonesia’s narcotics law. A normative juridical method is employed, utilizing statutory and case-based approaches. The analysis focuses on Law Number 35 of 2009 on Narcotics, alongside a detailed examination of the Court’s ratio decidendi in the selected decision. Legal materials are interpreted systematically to assess the alignment between formal legal provisions and their practical application in sentencing. The findings indicate that, while the Court maintains the legal classification of intermediary conduct as a criminal offense under narcotics law, it adopts a more nuanced approach in determining punishment. Specifically, the decision demonstrates a progressive application of sentencing principles by considering the offender’s level of involvement, degree of culpability, and the quantity of narcotics involved. This reflects an effort to move beyond rigid formalism toward a more context-sensitive adjudication. In conclusion, the study affirms that a just penal policy requires not only the fulfillment of legal elements but also the incorporation of substantive justice and utilitarian considerations. Such an approach is essential to prevent overcriminalization and to promote a more balanced, rational, and humane development of Indonesia’s narcotics penal system.